Portofolio Hasil Karya Berbasis Website - Wafa, Shidqul; Airlangga, Primaadi (Exact Papers in Compilation (EPiC), 2021)
Students who have completed their education and are ready to enter the job market need to know the importance of having a portfolio. because the company assesses the quality of applicants through a portfolio owned by job applicants. Some companies even recruit employees from portfolios regardless of educational background. While the problem of most students who are difficult to get a job is that students are not able to create their own portfolios properly. one solution that can be useful for students to support in terms of job search is a portfolio web application that can display the work of students. This application aims to provide a platform for students to be able to show off the work they create and can be a reference for a company to check the alignment of student skills for the work offered.